Completeness of death registration in Cape Town and its health districts, 1996-2004 - Zinyakatira, Nesbert (Division of Actuarial Science, 2016)
It is important for health planners to have timeous and accurate data on deaths. The Department of Home Affairs is responsible for the registration of deaths and the City of Cape Town has a well-established system of collating the death statistics based on vital registration, but the completeness of the death registration has not been assessed previously. The completeness was assessed for the City of Cape Town by comparing their statistics with an estimate based on data obtained from adult deaths reported in the 2001 census. A second approach assessed the trend in completeness between 1996 and 2004 by identifying three rates of mortality considered to be stable over time (non-lung and non-oesophageal cancers, the 10-14 age group and the 60+ age group) and inspecting to observe whether there was any trend apparent over time. Since deaths in most cases are under reported, and the under reporting usually differs in completeness between children and adults, child deaths from the ASSA model projection assuming that they are more complete were compared with the child deaths from the vital registration between 1996 and 2004 to check for completeness of the child vital registration data in Cape Town and its eight health districts The results show high levels of completeness in the adult deaths for Cape Town as a whole in 2001, around 95 per cent, but varying levels in the health districts. The completeness of reporting of male deaths in Cape Town declines with age, whilst completeness for females is fairly level with respect to age, with similar trends being observed in the health districts. Completeness of child (0 -4) death registration averaged around 60 per cent, about 35 per cent lower than the completeness of adult deaths in Cape Town. Cape Town as a whole and most of its health districts revealed two levels of completeness in the registration of deaths, 1996-1999 and 2001-2004 with 2000 sometimes consistent with the first and sometimes with the second period or different from either period in some of the health districts. In conclusion, the completeness estimates obtained are more rigorous from 2001 onwards suggesting that they can be reliably used to monitor trends in the levels of mortality in the city of Cape Town.